2003
DOI: 10.1051/apido:2003051
|View full text |Cite
|
Sign up to set email alerts
|

Sperm numbers in drone honeybees (Apis mellifera) depend on body size

Abstract: -The effect of drone honeybee's body size on semen production was evaluated. In the same colonies, drones were either reared in drone cells (large drones) or in worker cells (small drones). Wing lengths (size indicator) and sperm numbers of small and large drones were compared. Small drones (~13% reduced wing size) produce significantly fewer spermatozoa (7.5 ± 0.5 million) than normally sized drones (11.9 ± 1.0 million spermatozoa). There is a significant positive correlation between sperm number and wing siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
89
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(101 citation statements)
references
References 22 publications
8
89
2
Order By: Relevance
“…Thus, the impact on the drone body mass could only be observed in the laboratory experiment that included the possibility to perform foraging behaviour. For many insects body mass or size of males may interfere with the mating dynamics, sexual selection, reproductive potential and/or progeny production) [45][46][47] . Therefore, measures on body mass or size in the male progeny of bumblebees become an important sublethal effect.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the impact on the drone body mass could only be observed in the laboratory experiment that included the possibility to perform foraging behaviour. For many insects body mass or size of males may interfere with the mating dynamics, sexual selection, reproductive potential and/or progeny production) [45][46][47] . Therefore, measures on body mass or size in the male progeny of bumblebees become an important sublethal effect.…”
Section: Discussionmentioning
confidence: 99%
“…Whether diploid males always produce diploid spermatozoa, or not, remains unclear; FCM could greatly help in this respect. More generally, flow cytometry should allow testing various hypotheses on the evolution of mating systems in social insects, including possible variations in male sperm production or in strategies of sperm utilization by females (e.g., Wiernasz et al, 2001;Schlüns et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In all cited cases spermatozoa of vesiculae seminales of drones aged 11 or 12 day were counted. Schlüns et al (2003) counted 11.9 × 10 6 ± 1.0 × 10 6 spermatozoa in drones reared in drone cells. Drones reared in worker cells had an average of 7.5 × 10 6 ± 0.5 × 10 6 .…”
Section: Discussionmentioning
confidence: 99%
“…This variance in possibly fathering drones still is sufficient to contribute to differences in patriline proportions within colonies. Schlüns et al (2003) demonstrated that the size of A. mellifera drones has an influence on its sperm number. In this study spermatozoa numbers range from about one million up to 30 million spermatozoa among drones (aged 12 days) of 10 sister queens.…”
Section: Discussionmentioning
confidence: 99%